The Savvy Survey #6b: Constructing Open-Ended Items for a Questionnaire - Jessica L. Gouldthorpe; Glenn D. Israel (EDIS)
This 4-page fact sheet provides an overview of constructing open-ended items for a questionnaire. It is part of the Savvy Survey Series. Written by Jessica L. Gouldthorpe and Glenn D. Israel, and published by the UF Department of Agricultural Education and Communication, April 2014.